Pembelajaran Berbasis Masalah dalam Meningkatkan Kemampuan Analisis Siswa pada Mata Pelajaran Pendidikan Agama Islam - Suharnia Wati; Wianda Putri; Gusmaneli Gusmaneli (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
One of the important components in learning is the learning method. There are many types of learning methods, one of which is the problem-based learning method. The problem-based learning method is one of the active learning methods that can be applied by teachers when carrying out the learning process in the classroom. Through problem-based learning, students will be invited to learn independently, find information related to the problem, conduct discussions, find solutions in solving problems and can make conclusions. This article aims to find out how the implementation of problem-based learning methods to improve students' analytical skills in Islamic religious education subjects, the steps in applying problem-based learning methods and the factors that support and hinder the application of problem-based learning methods in Islamic religious education subjects at SMAN 10 Sijunjung. The method used in this research is field research through a qualitative approach with descriptive analysis of the data obtained through observation and interviews. The results of the research in this article are that teachers are able to apply problem-based learning methods through the right material, teachers are able to apply the steps and guide students with problem-based learning methods and teachers are able to overcome some of the obstacles faced in applying problem-based learning methods.